The Influence Of Celebrity Endorser Donna Agnesia On Buavita’s Television Advertising Towards Consumer Perceptions in Pekanbaru - Siti Nurbaya; Jushermi '; Aida Nursati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research was to determine the influence of using celebrity endorser Donna Agnesia on Buavita’s television advertising towards consumer perceptions in Pekanbaru. The population in this research are all consumer of Buavita products in Pekanbaru. The number of samples conducted by using Hair et al with 108 people respondents using purposive random sampling technique. Data analysis methodused is descriptive and quantitative methods using multiple linear regression analysis by SPSS version 18.0. From the results of simultaneous testing (F test), indicating that all independent variables studied, namely credibility, attractiveness and suitability of the celebrity endorser Donna Agnesia jointly have a very strong and significant influence towards consumer perceptions of Buavita products in Pekanbaru. Partial regression test (t test) indicates that the attractiveness variables have a dominant influence towards consumer perceptions of Buavita products in Pekanbaru.Keywords: Celebrity endorser, credibility, attractiveness, suitability, consumer perception